2022
DOI: 10.1111/1744-9987.13956
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors of catheter removal among 1062 episodes of peritoneal dialysis‐associated peritonitis: A multicenter 7‐year study

Abstract: Introduction: Studies focusing on catheter removal and the pathogenic spectrum of peritoneal dialysis-associated peritonitis (PDAP) need to be updated. Methods: Data were collected from four peritoneal dialysis (PD) centers. Peritonitis rates were compared using Poisson regression and Logistic regression was used to examine the risk factors for catheter removal. Results: The PD duration (odds ratio [OR], 1.021; 95% confidence interval [CI], 1.010-1.032), number of previous PDAP episodes (OR, 1.267; 95% CI, 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The average peritonitis rate was 0.225 episodes/patient-year in our study from 2013 to 2019, and per the ISPD recommendations updated in 2022, the requirement is no more than 0.4 episodes per patient-year, indicating that the incidence of peritonitis was relatively well controlled in the hospitals where this study was conducted. Another study from our center pointed out that the incidence of PDAP has decreased in recent years ( 18 ), and our study also observed that the incidence of MDRO-PDAP was similarly decreasing between 2013–2019. However, MDRO-PDAP remains a serious challenge for clinicians because of increasing drug resistance among bacteria.…”
Section: Discussionsupporting
confidence: 81%
“…The average peritonitis rate was 0.225 episodes/patient-year in our study from 2013 to 2019, and per the ISPD recommendations updated in 2022, the requirement is no more than 0.4 episodes per patient-year, indicating that the incidence of peritonitis was relatively well controlled in the hospitals where this study was conducted. Another study from our center pointed out that the incidence of PDAP has decreased in recent years ( 18 ), and our study also observed that the incidence of MDRO-PDAP was similarly decreasing between 2013–2019. However, MDRO-PDAP remains a serious challenge for clinicians because of increasing drug resistance among bacteria.…”
Section: Discussionsupporting
confidence: 81%
“…[ 15 ] and Liu et al. [ 12 ] reported that dialysate leukocyte count >100 × 10 6 /L on day 5 is a predictor of treatment failure and catheter removal in patients with PDAP. In the ISPD guideline 2022s, refractory peritonitis was defined as failure of the PD effluent to clear after 5 days of appropriate antibiotics, and PD catheter removal was recommended for this situation to prevent morbidity and mortality associated with treatment failure, although the evidence underpinning this recommendation is limited [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While prior literature has suggested a potential reduction in peritonitis risk in APD patients, our research uncovered a statistically significant difference, with 56.0% of cases occurring in APD compared to 44.0% in CAPD (p < 0.001). The observed variation prompts further inquiry into factors that may contribute to these differences, including patient demographics, adherence to aseptic techniques, and the potential impact of the automated nature of APD [28,29]. Understanding and addressing these nuances in peritonitis risk across peritoneal dialysis modalities is crucial for optimizing patient care and outcomes in the long-term management of end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%